1999
DOI: 10.1046/j.1365-2958.1999.01637.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Escherichia coli NRZ nitrate reductase is highly growth phase dependent and is controlled by RpoS, the alternative vegetative sigma factor

Abstract: SummaryIn the absence of oxygen, many bacteria preferentially use nitrate as a terminal electron acceptor for anaerobic respiration. In Escherichia coli, there are two membrane-bound, differentially regulated nitrate reductases. While the physiological basis for this metabolic redundancy is not completely understood, during exponential growth, synthesis of NRA is greatly induced by anaerobiosis plus nitrate, whereas NRZ is expressed at a low level that is not in¯uenced by anaerobiosis or nitrate. In the course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…The NarZYV enzyme contributed little to the overall nitrate reductase activity (compare the activities of strains VJS5435 and VJS5437), as expected since low levels of this enzyme are synthesized during exponential growth (10). The NarG ϩ NapA ϩ strain VJS5432 exhibited significant endogenous activity, which increased fourto fivefold when reduced viologen was provided as an artificial electron donor.…”
Section: Resultsmentioning
confidence: 51%
“…The NarZYV enzyme contributed little to the overall nitrate reductase activity (compare the activities of strains VJS5435 and VJS5437), as expected since low levels of this enzyme are synthesized during exponential growth (10). The NarG ϩ NapA ϩ strain VJS5432 exhibited significant endogenous activity, which increased fourto fivefold when reduced viologen was provided as an artificial electron donor.…”
Section: Resultsmentioning
confidence: 51%
“…In contrast, the third, nitrate reductase Z, is expressed during exponential growth at such a low level that it contributes insignificantly to the total rate of nitrate reduction when either of the other two enzymes is also expressed. However, in both E. coli and S. typhimurium, its synthesis is induced under the control of RpoS during the stationary phase of growth (Chang et al, 1999;Spector et al, 1999). In this study, we demonstrated that NarU also accumulates during the stationary phase rather than during exponential growth, that its synthesis confers a selective advantage during nutrient starvation or very slow growth, and that narU is cotranscribed with narZ, implicating narU as the first gene of a five-gene polycistronic narUZYWV operon.…”
Section: Discussionmentioning
confidence: 61%
“…The third nitrate reductase, encoded by the narZYWV operon, is structurally very similar to nitrate reductase A Bonnefoy et al, 1997), but is expressed extremely weakly during both aerobic and anaerobic growth (Iobbi et al, 1987). Although expression of nitrate reductase Z is induced during entry into the stationary phase of growth, its activity is still at the lower limits of detection by most biochemical assays (Iobbi-Nivol et al, 1990;Bonnefoy et al, 1997;Chang et al, 1999;. Consequently, nitrate reductase Z contributes very little to the overall rate of nitrate reduction by E. coli, and is sufficient to support only a very low rate of nitrate-dependent anaerobic growth with glycerol as the non-fermentable carbon source .…”
Section: Introductionmentioning
confidence: 99%
“…This was found to be important, as many of the genes identified have paralogous functions whose activity may be masked by the presence of another gene product (e.g., NarG or NarZ). There are several published RpoS-dependent paralogs, including NarZ (nitrate reductase) (18) and Ldc (lysine decarboxylase) (89), that comprise only a small percentage of the cell's total activity. There are many other paralogous functions that are controlled by RpoS, and collectively this suggests that expressing a subset of key duplicated metabolic functions is an important physiological imperative in stationary-phase cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrate reductase Z is encoded by members of the nar-ZYWV operon (71). The RpoS-dependent narY gene codes for the beta subunit of nitrate reductase Z, which functions as an electron acceptor during anaerobic growth on nitrate in E. coli (18).…”
Section: Vol 186 2004mentioning
confidence: 99%